A New Analytical Method for Extracting Precise Structural Parameters of Epitaxial Graphene from Moiré Patterns. Issue 24 (7th November 2016) - Lim, Hyunseob; Yang, Hyun Jin; Kim, Yousoo
Abstract : A new analytical method to determine the most important two parameters, rotational angle ( Rθ ) and strain (Δ a Gr / a Gr ) of graphene on metal substrate, from scanning tunneling microscope images is presented. Epitaxial graphene on Ir(111) and Pt(111) was investigated by this method, which demonstrates that rotational angle and strain are not independent factors. Rather, these components influence each other to stabilize the graphene–metal interaction thermodynamically.